Keeping up with the Joneses by finding a better-paid job - The effect of relative income on job mobility - Kristin Kronenberg; Tobias Kronenberg (European Regional Science Association (ERSA), 2011)
It has been shown that a person's relative income - compared to a reference group - has a negative impact on self-reported happiness. This suggests that people who aim at increasing their happiness should try to find a better-paid job if their relative income is low. In this paper we study this hypothesis by estimating the effect of relative income on job mobility, using a dataset containing information on roughly four million Dutch employees. We consider three different reference groups: people who live in the same neighborhood, people who work for the same employer, and people who share certain demographic characteristics. Our findings suggest that workers compare their own income to that of their neighbors, and low relative income is associated with higher job mobility. We conclude that low relative income (compared to the neighbors) reduces workers' happiness, and workers react to this by finding a new job which may offer the prospect of higher pay.
Keywords: 330